RETRACTED: Problems in the development of Russian agricultural producers as the rural tourism market participants - Shcherba Lidia; Oleynikova Yulia (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001